2016
DOI: 10.3389/fimmu.2016.00470
|View full text |Cite
|
Sign up to set email alerts
|

Milestones of Hematopoietic Stem Cell Transplantation – From First Human Studies to Current Developments

Abstract: Since the early beginnings, in the 1950s, hematopoietic stem cell transplantation (HSCT) has become an established curative treatment for an increasing number of patients with life-threatening hematological, oncological, hereditary, and immunological diseases. This has become possible due to worldwide efforts of preclinical and clinical research focusing on issues of transplant immunology, reduction of transplant-associated morbidity, and mortality and efficient malignant disease eradication. The latter has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 183 publications
(209 reference statements)
0
84
0
5
Order By: Relevance
“…Existing tumor‐reactive CTLs in non–T‐cell‐depleted grafts are responsible for the induction of GVT effects . We showed that the initial frequencies of MART1‐reactive CTLs were similar in both T‐cell sources, but the CB CTLs were primarily naïve (CCR7+CD45RA+) while the PB CTLs had a mixed phenotype consisting of naïve (59%) and memory CD45RA– (34%) T cells.…”
Section: Discussionmentioning
confidence: 80%
“…Existing tumor‐reactive CTLs in non–T‐cell‐depleted grafts are responsible for the induction of GVT effects . We showed that the initial frequencies of MART1‐reactive CTLs were similar in both T‐cell sources, but the CB CTLs were primarily naïve (CCR7+CD45RA+) while the PB CTLs had a mixed phenotype consisting of naïve (59%) and memory CD45RA– (34%) T cells.…”
Section: Discussionmentioning
confidence: 80%
“…HSCT improves disease‐free survival for hematologic childhood malignancies and is either a last resort when other treatments have failed or as initial therapy for particularly aggressive diagnoses . Myeloablative conditioning regimens that include TBI and chemotherapy accomplish the dual goals of eradicating underlying malignant cells and providing immunosuppression to maximize rates of engraftment …”
Section: Total Body Irradiation and Hematopoietic Stem Cell Transplanmentioning
confidence: 99%
“…The use of fractionated TBI has become standard and involves delivering multiple (six to eight) relatively small doses over 3–4 days for a total dose of 12–14 Gy . This approach maximizes the effect on malignant cells by allowing a higher total irradiation dose while simultaneously reducing the rate of tissue morbidity …”
Section: Total Body Irradiation and Hematopoietic Stem Cell Transplanmentioning
confidence: 99%
See 1 more Smart Citation
“…About 200 trials were made between 1959 and 1962; however none of the recipient became long time survivors [15]. It seems that the unsuccessful allogeneic bone marrow transplantations were due to poor histocompatibility typing available, lack of effective supportive care such as antibiotics, lack of transfusional support with platelets and to the TBI protocol that was not so effective to achieve the immunosuppression necessary [1,[16][17][18].…”
Section: The Early Daysmentioning
confidence: 99%